Nutritional Care for Pediatric Patients with Severe Hypokalemia Et Causa Suspected Gitelman dd Bartter Syndrome + Severe Protein Energy Malnutrition Marasmus Type Rehabilitation Phase in PHCU Violet Room at Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar - Mirayanthi, Luh Putu; Sulatri, Ni Luh; Fanny, Lydia; Mas’ud, Hikmawati (LPPM Universitas Dhyana Pura, 2025)
Severe hypokalemia is a critical emergency that often occurs in children with severe malnutrition, such as marasmus. This condition is exacerbated by genetic syndromes such as Gitelman or Bartter, which cause impaired potassium reabsorption in the kidneys. Pediatric patients with severe Protein Energy Malnutrition (PEM) who suffer from hypokalemia are in a very vulnerable condition and are at high risk of experiencing serious, even life-threatening complications. The combination of these two conditions exacerbates disorders in various body systems. The purpose of this study was to carry out the Standardized Nutrition Care Process management in pediatric patients with severe hypokalemia et causa suspected Gitelman Syndrome and Bartter Syndrome with severe PEM (Protein Energy Malnutrition) type marasmus rehabilitation phase in the PHCU Room of Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar. This type of research is a descriptive observational study with a case study method, starting from nutritional screening, nutritional assessment, intervention, monitoring and evaluation. At the initial observation before the intervention, the patient was categorized as high-risk for malnutrition, with inadequate oral intake, low potassium test results, and general physical weakness. The nutritional intervention provided was a 2000 kcal + high-potassium pediatric diet, consisting of regular food modified with commercial enteral fluids. The diet was administered in stages starting at 60% of the requirement. Observations showed an increase in energy and nutrient intake over 5 days, potassium test results returned to normal, and clinical physical symptoms began to improve. After receiving nutrition education, the patient and his family understood and were willing to follow the recommended diet.